Study of the relationship between the economic growth, foreign direct investment, the intensity of R&D and corruption on environmental pollution. The case of Kazakhstan (Journal of Economic Research & Business Administration, 2018)
Investment is a driver of socio-economic transformation of any countries. FDI in emerging marketeconomy can be mutually beneficial both: for the host country and transnational corporations. In the hostcountry, transnational corporations provides further financial resources through investments and taxes,creates jobs and generates spillovers such as the knowledge sharing, technology, management skills andcorporate governance practices. On the other hand, TNCs get access to local market, natural resourcesrelated to specific objects, low labor resource costs and take advantage of bilateral and multilateral tradepolicies.In this paper, we have made a preliminary analysis on the situation of the relationship between theeconomic growth and the level of environmental pollutions in Kazakhstan. There is a gap in researchabout the relationship between these variables in developing countries, especially between the territoriesof the former Soviet Union. We have also been interested in analyzing whether, the perceivedlevel of corruption and the intensity of research and development activities moderate this relationship,as their study in these economies not carried out. The special interest is to analyze does the investmentby transnational corporations in these countries is helping or not to reduce environmental pollutions.